Experiencing Climate Change: Phraseological Patterns of Perception Verbs in GenZ Climate Activism Online - Falcone, Mariasophia (Status Quaestionis, 2024)
Climate change has impacted profoundly today’s younger generations, primarily GenZ, shaping their worldview through first-hand experiences of environmental challenges. In response, younger people have recently mobilized, sparking a resurgence in environmentalism and an increased engagement in climate discourse on the web. Perception verbs, by indicating the sensory mode of information acquisition, are used by speakers to express what they perceive, grounding statements in personal experience and observation. Consequently, the study presents an analysis of phraseological patterns of perception verbs in a corpus of web texts from three GenZ environmental organizations to understand their perception of climate change and climate-related issues. Initially, the occurrence of perception verbs in the dataset is explored quantitatively. Subsequently, 4- and 5-grams are analysed to investigate their phraseology. Results reveal a key presence of perception verbs used predominantly to understand and communicate the complexities of climate issues, reflecting the peculiar engagement of young activists with climate change.